EFFECT OF PRIMING SOLUTIONS IMPROVEMENT ON METABOLISM ASSOCIATED WITH CARDIOPULMONARY BYPASS - Cherniy, V.I.; Sobanska, L.O.; Topolov, P.O. (World of Medicine and Biology, 2023)
Improving metabolism by optimizing the composition of the priming during on-pump coronary artery bypass grafting was the aim of this study. The 30 patients were divided into two groups. In group 1, priming included succinated gelatin 4 %, mannitol 15 %, Soda buffer 4.2 %, Reosorbilact, heparin. In group 2, priming included succinated gelatin 4 %, mannitol 15 %, sodium bicarbonate 4 %, 0.9 % sodium chloride, heparin. It has been shown that cardiac patients have preoperative metabolic disorders. In group 1 the metabolic rate index was 425.61±27 kcal/min/m², and the target metabolic index was 576.79±16 kcal/min/m². In group 2, 355.98±32 kcal/min/m² and 689.28±21 kcal/min/m², respectively. In group 1, the metabolic rate index metabolism was differed from the target by 27 %, and in group 2 – by 52 %. One of the methods for improving perioperative metabolism is the optimization of the priming composition under the control of energy monitoring.